The acoustic power of a circular plate excited by non-uniform surface pressure - SZEMELA, K.; RDZANEK Jr., W. P.; RDZANEK, W. (Archives of Acoustics, 2006)
This work is focused on the analysis of the influence of a non-uniformly distributed surface excitation on sound radiation by a clamped circular plate embedded in a flat rigid baffle. It is assumed that the vibrations and radiations are axisymmetric and time-harmonic, moreover, the losses of energy into the plate's material are neglected. The influence of the surrounding medium on the vibration of the plate is not taken into account. The distribution of the exciting pressure is assumed in the form of a function whose shape can be modeled by fitting suitable values of parameters. The approximation of the distribution of the forcing pressure by the use of an analytical function makes it possible to consider practical cases. Integral formulae for describimg the active power have been obtained. The solution of the equation of motion is achieved by employing an expansion into series of eigenfunctions. An analysis of the influence of the parameters characterizing the surface excitation on the radiation power has also been presented. The low and high frequency elementary form asymptotics can be obtained by using the reached herein formulae and the known approximated expressions.